How the CLEANED tool is assessing livestock environmental impacts in the dairy sector in Tunisia for sustainable, profitable management - van der Hoek, Rein; Paul, Birthe K.; Gloy, Nele; Masmoudi, Ahlem; Moujahed, Nizar; Marouani, Wahid; Werghi, Imed; Notenbaert, An Maria Omer (Bioversity International and the International Center for Tropical Agriculture, 2024)
How the CLEANED tool is supporting informed decisions on the dairy sector by the Ministry of Agriculture, NARS and development partners. The potential environmental impacts of the transformation of the dairy value chain were assessed through a collaboration between the Alliance of Bioversity International and CIAT, ICARDA, GIZ and national partners.